2016
DOI: 10.1590/1809-4392201600204
|View full text |Cite
|
Sign up to set email alerts
|

Oleanonic acid from Lippia lupulina (Verbenaceae) shows strong in vitro antileishmanial and antitrypanosomal activity

Abstract: Leishmaniasis and Chagas disease affect millions of people in tropical and subtropical regions. Drugs used currently to treat such diseases often present undesirable side effects and low efficiency. The aim of this work was to identify extracts and isolated compounds from the genus Lippia with leishmanicidal and trypanocidal activity. , respectively). The triterpenoid oleanonic acid showed the strongest activity against these protozoans (IC 50 of 18.5 and 29.9 µM, respectively). Our results indicate that Lippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…iowensis DSM 45197 as biocatalysts of the OA (approximately 0.3 g/L) transformation process for 13 days resulted in the formation of methyl OA ( 91 ) as the main bioconversion product (more than 60.0%), small amounts (≤5.0%) of methyl 3-oxo-olean-12-en-28-oat ( 92 ), and metabolite 93 unidentified by the authors [ 16 ]. 3-oxo-OA ( 92 ) was shown to have pronounced antimelanoma [ 124 ], antileishmanial, and antitrypanosomal effects [ 125 ]. Despite numerous successful examples to increase the efficiency of the biotransformation process by immobilizing microbial cells [ 126 ], the use of fixed Nocardia cells in alginate carriers led to a decrease in their catalytic activity, as confirmed by a 10-fold decrease in the formation of compound 91 and only a short-term occurrence of compound 93 in the culture medium [ 16 ].…”
Section: Biological Transformationmentioning
confidence: 99%
“…iowensis DSM 45197 as biocatalysts of the OA (approximately 0.3 g/L) transformation process for 13 days resulted in the formation of methyl OA ( 91 ) as the main bioconversion product (more than 60.0%), small amounts (≤5.0%) of methyl 3-oxo-olean-12-en-28-oat ( 92 ), and metabolite 93 unidentified by the authors [ 16 ]. 3-oxo-OA ( 92 ) was shown to have pronounced antimelanoma [ 124 ], antileishmanial, and antitrypanosomal effects [ 125 ]. Despite numerous successful examples to increase the efficiency of the biotransformation process by immobilizing microbial cells [ 126 ], the use of fixed Nocardia cells in alginate carriers led to a decrease in their catalytic activity, as confirmed by a 10-fold decrease in the formation of compound 91 and only a short-term occurrence of compound 93 in the culture medium [ 16 ].…”
Section: Biological Transformationmentioning
confidence: 99%
“…The isolated compounds (Holaphylline, Saracodine) were evaluated for anti-leishmanial activity. From the viable promastigotes, bulk culture (3.7×10 7 /mL), 1×10 5 promastigotes/well in 200 µL fresh M-199 medium were seeded in 96-well plate. Four concentrations of the compounds were prepared and the control was placed in one row of 12 wells having only the growth medium.…”
Section: Anti-promastigote Potential For Isolated Compoundsmentioning
confidence: 99%
“…Plant based medicines are being claimed as one of the important source for the development of drug in treating leishmaniasis diseases. 5 Many research studies showed that many plants extract and thire derived possess anti-leishamanial activity against different species of Leishmania. 5 In the same way one of the plant belongs to Sarcococca species of Buxaceae family have rich source of steroidal alkaloids that possess different biological activities in endemic region of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrum of the obtained compound corresponded to the mass spectrum of the methyl ester of 3-oxo-olean-12-en-28-oic acid. It is known that 3-oxo-olean-12-en-28-oic acid has a pronounced in vivo antimelanoma [7] and in vitro antileishmanial and antitripanosomal effects [8]. The literature describes the formation of 3-oxoolean-12-en-28-oic acid using actinobacteria Nocardia iowensis DSM 45197 as a biocatalyst.…”
mentioning
confidence: 99%